1987
DOI: 10.1152/ajprenal.1987.252.3.f480
|View full text |Cite
|
Sign up to set email alerts
|

Resetting of renal blood flow autoregulation in spontaneously hypertensive rats

Abstract: Renal blood flow (RBF) autoregulation was examined in untreated 10- and 40-wk-old spontaneously hypertensive rats (SHR) [mean arterial pressure (MAP) 125 +/- 4 and 167 +/- 7 mmHg] and in captopril-treated (7 days) 10- and 40-wk-old SHR (88 +/- 7 and 112 +/- 5 mmHg). Age-matched Wistar-Kyoto rats (WKY) were used as controls (MAP 91 +/- 3 and 104 +/- 2 mmHg). The study was carried out in rats with and without acute uninephrectomy. In 10-wk-old acutely uninephrectomized animals, the lower pressure limit of autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 0 publications
8
52
1
Order By: Relevance
“…2 In previous studies with the isolated perfused hydronephrotic kidney, we demonstrated that pressure-induced afferent arteriolar vasoconstriction is reset to higher pressure levels in SHR. 3 In the present study, alterations in the myogenic responsiveness of the intermediate segment of the ILA were observed to occur in this same model.…”
Section: Altered Pressure Response Of the Interiobular Artery In Sponmentioning
confidence: 73%
See 1 more Smart Citation
“…2 In previous studies with the isolated perfused hydronephrotic kidney, we demonstrated that pressure-induced afferent arteriolar vasoconstriction is reset to higher pressure levels in SHR. 3 In the present study, alterations in the myogenic responsiveness of the intermediate segment of the ILA were observed to occur in this same model.…”
Section: Altered Pressure Response Of the Interiobular Artery In Sponmentioning
confidence: 73%
“…2 We have previously demonstrated that myogenic afferent arteriolar vasoconstriction is reset to higher renal arterial pressure (RAP) levels in spontaneously hypertensive rats (SHR). 3 Although the afferent arteriole is primarily responsible for both acute 4 -5 and chronic 6 ' 7 adaptations to elevated RAP, the interlobular artery (ILA) may also contribute to renal autoregulation.…”
mentioning
confidence: 99%
“…Changes in perfusion pressure were corrected for by ϳ85-90% under baseline conditions. This finding is in contrast to reports showing almost perfect autoregulatory efficiency in the SHR (16). The present data set was subjected to the same calculation method described previously (27), which avoids interobserved error, as has been recently emphasized by others (9).…”
Section: Discussionmentioning
confidence: 94%
“…On the one hand, renal NO dependency has been reported to be increased (29), which could lead to a diminished autoregulatory efficiency. On the other hand, RBF autoregulation is preserved relatively well in the SHR, albeit at a higher range of perfusion pressures (1,16,21). The influence of NO on autoregulation in this model has been investigated in one study (19).…”
mentioning
confidence: 99%
“…The activity of the renin-angiotensin system (RAS) is normal or low in SHR [31] . However, the BP can be lowered by the commonly used ACE inhibitor and AT 1 receptor blockers [32,33] . This is consistent with our present results that allisartan reduced BP in SHR.…”
Section: Discussionmentioning
confidence: 99%